Conceptual Metaphors in Pedagogical Discourse - Dadajonova , Kabira; Yunusova, Hilola (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
This paper investigates the role of conceptual metaphors in pedagogical discourse from a cognitive linguistic perspective. It argues that metaphors are not only linguistic devices but also cognitive tools that structure understanding, guide teaching strategies, and shape learners’ perception of knowledge. The study analyzes commonly used conceptual metaphors in educational settings and discusses their pedagogical implications.